2017
DOI: 10.1371/journal.pone.0171152
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk of diabetes seriously underestimates actual diabetes risk: The KORA FF4 study

Abstract: ObjectiveEarly detection of diabetes and prediabetic states is beneficial for patients, but may be delayed by patients´ being overly optimistic about their own health. Therefore, we assessed how persons without known diabetes perceive their risk of having or developing diabetes, and we identified factors associated with perception of diabetes risk.Research design and methods1,953 participants without previously known diabetes from the population-based, German KORA FF4 Study (59.1 years, 47.8% men) had an oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 33 publications
5
47
1
5
Order By: Relevance
“…All participants without previously known diabetes took part in a standard oral glucose tolerance test (OGTT) and their glucose tolerance status was classified according to the 2003 American Diabetes Association (ADA) diagnostic criteria [28]. Further details have been outlined elsewhere [29]. An OGTT value of ≥ 7.0 mmol/L fasting or ≥ 11.1 mmol/L 2-h glucose was defined as undetected diabetes mellitus (UDM), also called screen-detected diabetes.…”
Section: Assessment Of Glucose Tolerance Statusmentioning
confidence: 99%
“…All participants without previously known diabetes took part in a standard oral glucose tolerance test (OGTT) and their glucose tolerance status was classified according to the 2003 American Diabetes Association (ADA) diagnostic criteria [28]. Further details have been outlined elsewhere [29]. An OGTT value of ≥ 7.0 mmol/L fasting or ≥ 11.1 mmol/L 2-h glucose was defined as undetected diabetes mellitus (UDM), also called screen-detected diabetes.…”
Section: Assessment Of Glucose Tolerance Statusmentioning
confidence: 99%
“…the way content is presented), targeted according to the health literacy and media use of the population, as well as visualisation or the use of narratives are evidence-based communication strategies [23]. Communication campaigns have proven effective in improving disease-specific health literacy [24], persuading high-risk populations to take part in screenings [25], increasing patients' physical activity levels [26], promoting a healthy diet [27] and improving social support for patients with diabetes [28]. When used to accompany policy initiatives, communication strategies can reduce resistance and improve overall acceptance of the initiatives [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Nigeria among university staff showed a risk perception of 67% for non-communicable diseases while good knowledge of diabetes was shown to be 30% among diabetic patients in another study (17,20). However, family members of individuals with type 2 diabetes underestimate their risk of developing the disease (21,22).…”
Section: Discussionmentioning
confidence: 99%